PRINSIP-PRINSIP SOPAN SANTUN DALAM BAHASA INGGRIS DAN BAHASA TONDANO (ANALISIS KONTRASTIF) - Palilingan, Kezia Pricilia Patricia; Lasut, Theresia M.C; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTÂ Â Â This research is entitled â€œPoliteness Principles in English and Tondano language: A Contrastive Analysis.â€. The aims of this research are identify, classify, and analyze the politeness principles in the forms of politeness maxims, which are used by Tondano society. The research questions to be answered namely what are the types of politeness principles in English and Tondano languages and to find out the similarities and differences in the both languages. In terms of the methodology, this research has been done through library and field studies by using the qualitative method and contrastive analysis. The data of both languages are analyzed based on the theory of Leech (1983) and Whitman (1970). It is found that the concepts of politeness in English and Tondano languages are vary. The result of this research shows that politeness principles in English and Tondano language have the similarities and differences. The similarities, for example, can be found in the forms of politeness maxims of each language. The differences, for example, can be found in the form of words usage of each language, and based on the form of the polite utterances in English and Tondano language have asking, order, and command meanings.Keywords: Politeness, English and Tondano Languages, Contrastive